How to lockdown an economy: An Input Output analysis of the Italian case - Paolo Manasse; G. Alfredo Minerva; Roberto Patuelli; Lorenzo Zirulia (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2020)
This paper employs the most recent Input Output tables to discuss the Italian lockdown after the COVID-19 epidemics. We define "basic activities" and derive a ranking of industries which more intensively contribute to them. Confronting our results with the choices of the Italian government, we find that these were broadly correct in terms of industrial composition. However, we find that the lockdown of industries such as construction, real estate and manufacture of basic metals reveal a very conservative preferences in terms of the target share of output of essential activities (below 85 %).
Keywords: D57; L52; L60; 330; COVID-19; epidemic; lockdown; input-output